An Electrospun Nanofibrous Sensor Based on a Porous (Cr/Zn) Slats Oxide for Voltammetric Detection of Ezetimibe Drug in Real Samples. Issue 10 (4th August 2021) - Elfiky, Mona; Matsuda, Atsunori; Salahuddin, Nehal
Abstract: Herein, a series of bimetallic slats oxide nanofibers with different molar proportions of Cr: Zn were synthesized via the electrospinning method. Nanofibers with a molar proportion of (Cr: Zn=1: 2) [CrZn3 ] demonstrated a large superficial area (123.3 m 2 /g) with minimal resistivity. A modulated carbon paste sensor (MCPS) constructed using 1.0 % of [CrZn3 ] exhibited remarkable surface electrocatalytic activity for oxidation of ezetimibe drug and oxidation reduction of an electroactive probe (K3 [Fe(CN6 )]). Under optimized conditions, the limit of the detection of the obtained MCPS for ezetimibe in bulk form was 0.024 nmol L −1 and its linear range was 0.08–1.5 nmol L −1 . The sensor also demonstrated good selectivity toward the drug in human medication and serum fluid. Abstract :